Hubungan Tingkat Kecukupan Zat Besi Dan Seng Dengan Kejadian Stunting Pada Balita 6-23 Bulan - Enggar Kartika Dewi; Triska Susila Nindya (Amerta Nutrition, 2017)
Background: Stunting is a cronic malnutrition that affects linear growth. The main cause of malnutrition is the adequacy of micronutrients in the process of linear growth. Micronutrients that relate to stunting are iron and zinc, because both of that micronutrient have necessary role in linear growth of toddlers age 6 -23 months. Objectives: The purpose of this study was to analyze correlation between iron and zinc adequacy level with stunting incidence in toddlers age 6 -23 months. Methods:  This study was an analytical study with cross sectional design. The sample size were 55 children spread over 25 Posyandu in Suci Village. The data collected using of food recall 3x24 hours, height measurement with microtoice for stunting status, and the questionnaire characteristics of children and mothers. The data were analyzed by using Fisher's Exact test. Result: The results showed 14.5% of toddlers age 6 – 23 months were stunted. 33.3% of children were given inadequate iron intake and 35.7% of children were given inadequate zinc intake. The analysis test showed there was a significant correlation between levels of iron and zinc adequacy with the incidence of stunting with p=0.02 and p=0.018. Conclusion: The proportion of stunting will increase if the toddler were given inadequate of iron and zinc. Education about the adequacy levels of iron and zinc for toddler age 6-23 months were adjusted to reduce and avoid stunting.ABSTRAK Latar Belakang: Stunting merupakan masalah gizi akibat kekurangan gizi jangka panjang yang berdampak pada pertumbuhan linier. Salah satu zat gizi mikro yang erat kaitannya dengan stunting adalah zat besi dan seng, sebab kedua zat mikro tersebut memiliki peran penting dalam pertumbuhan linier balita 6-23 bulan.Tujuan: Tujuan dari penelitian ini adalah untuk menganalisis hubungan tingkat asupan zat besi dan seng dengan kejadian stunting pada balita 6-23 Bulan.Metode: Penelitian ini merupakan jenis penelitian observasional analitik dengan desain penelitian cross sectional. Sampel terdiri dari 55 anak yang tersebar di 25 Posyandu di Desa Suci. Pengumpulan data menggunakan food recall 3x24 jam, pengukuran tinggi badan dengan mikrotoa untuk mengetahui status stunting, dan kuesioner karakteristik anak dan ibu. Data dianalisis menggunakan uji Fisher’s Exact.Hasil: Hasil penelitian menunjukkan 14,5% balita usia 6-23 bulan mengalami stunting, 33,3% anak memilliki tingkat kecukupan zat besi yang kurang dan 35,7% anak memiliki tingkat kecukupan seng yang kurang. Uji statistik menunjukkan terdapat hubungan yang signifikan antara tingkat kecukupan zat besi dan seng dengan kejadian stunting dengan p=0,02 dan p=0,018.Kesimpulan: Proporsi stunting akan meningkat jika tingkat kecukupan zat besi dan seng inadekuat. Sebaiknya dilakukan peningkatan edukasi tentang tingkat kecukupan zat besi dan seng untuk balita usia 6-23 bulan yang bertujuan untuk mengurangi dan mencegah stunting.